A Comprehensive study on Brain Mechanisms for Language Acquisition and Comprehension - Kailash Nath Tripathi, Anand Bihari, Sudhakar Tripathi, R. B. Mishra (Mathematical Statistician and Engineering Applications, 2021)
This study intends to bring the main viewpoint of language acquisition and language comprehension. We have reviewed the different types of language acquisitions like first, second, sign, and skill. The experimental techniques for neurolinguistic acquisition detection are discussed. The findings of experiments for language acquisition are analysed, which involves the brain region activated after the acquisition. It demonstrates the different types of language acquisition involve other areas of the brain. In language comprehension, native language comprehension and bilingual’s comprehension have been considered. Comprehension involves different brain regions for a different sentence or word comprehension, depending upon their semantic and syntax. This review has also addressed the other fMRI /EEG analysis techniques (statistical/ graph theoretical). Neurolinguistic computational tools (pre-processing/computations/analysis) and varied computational techniques for neuro data are also explained.